Diretrizes para conservação da espécie Mimosa Caesalpiniifolia Benth., Macaíba-RN - Souza, Clarice Sales Moraes de (2012)
About 40% of the earth is occupied by tropical and subtropical forests, including 42% of dry forests, where there is Caatinga Bioma, contemplating tree forests and shrubs, with xerophytic characteristics. Study and conservations of Caatinga biologic diversity is one of the greatest challenges of Brazilian science because those are, proportionally, the less studied among natural areas, with most of the scientific effort centered in very few points around the main cities in the area and also because it is the less protected natural Brazilian area. The environmental degradation is constantly increasing and has its rhythm accelerated by the men appropriation to meet or not their own needs. Therefore, species conservation should be based in three principles: the use of natural resources by present generation, waste prevention and use of the natural resources to benefit the majority of the citizens. Among the strategies to species conservation, we can mention the ex situ conservation , in which the conservation of genetic resources may be realized outside of the natural environment in which the species occur, and in situ conservation , or, in other words, in the places where the species occur. In ex situ conservation, the germplasm collections are maintained in the field and/or in laboratories (conservation chambers), and this mainly conserves intraspecific diversity (genetic variance), the ex situ collections are continuously enriched by collection activities, introduction and germplasm interchange; the in situ conservation preserving ecosystems and habitats, maintaining and recovering native population of species of interest. So, the objective of this paper is the search for strategies to the conservation of Mimosa caesalpiniifolia B. (sabiá) using instruments of environmental perception and plant biotechnology, as mechanisms of in situ and ex situ conservation. To environmental perception, were realized open, semi-structured and qualitative interviews. The questions included socioeconomic data and knowledge of Sabiá specie. To plant biotechnology, Sabiá seed collection were realized in different location to formation of a germplasm bank. The specie micropropagation was made from nodal segment of plants from the matrizeiro. About the knowledge of rural populations and the use of Sabiá plant, some preferences occurred from speeches that the plant possesses a firm wood, not attacked by termites, legalized for exploration by the Brazilian environmental organ (IBAMA), and is a native specie. This research found the rural population has knowledge about Sabiá specie and the natural resources are exhausting. The proposal that the rural community brought was the donation of the Sabiá specie seeding initiating on the rain season, in which the seeding would be plated between the lots, in individual plantations. To the formation of a matrix bank, plant biothecnology brought answers favorable to Sabiá specie seeding, with the formation of multiple shoots